Integrative Analysis of Differential lncRNA/mRNA Expression Profiling in Helicobacter pylori Infection-Associated Gastric Carcinogenesis - Li, Nianshuang; Ouyang, Yaobin; Chen, Sihai; Peng, Chao; He, Cong; Hong, Junbo; Yang, Xiaoyu; Zhu, Yin; Lu, Nong-Hua (Frontiers in Microbiology, 2020)
Helicobacter pylori (H. pylori) infection is the greatest known risk factor for gastric cancer (GC). Long noncoding RNAs (lncRNAs) are implicated in multiple biological processes. However, their contribution in H. pylori-associated GC remains largely unknown. We performed transcriptome sequencing to investigate differential lncRNA and mRNA expression profiles in gastric AGS cells infected with the H. pylori strain 7.13 or 43504. We identified significantly differentially expressed (SDE) mRNAs and lncRNAs following H. pylori infection. A co-expression network of lncRNAs and mRNAs was constructed via WGCNA analysis. Moreover, several of the most significantly upregulated genes were selected for further validation by qRT-PCR analysis in H. pylori-infected gastric cells and transgenic INS-GAS mice. We finally evaluated these genes in human GC tissues. A total of 158442 genes were identified between uninfected and infected cells. Of these, 298 mRNAs and 73 lncRNAs were consistently differentially expressed following infection with the H. pylori 7.13 and 43504 strains, respectively. The expression levels of most upregulated mRNAs (DDIT4, NDRG1, CHAC1, IL32, RELB, CTH, and SLC7A1) and lncRNAs (lncRNA36068, lncRNA51663, lncRNA49853, lncRNA49852 and FLJ46906) were validated by qRT-PCR analysis. We found that H. pylori infection significantly induced the transcript levels of the coding genes RELB and SLC7A11 in in vitro and in vivo assays, which was supported by their high expression levels in GC tissues. In addition, lncRNA51663 and FLJ46906 were remarkably increased in H. pylori-infected cells and consistently overexpressed in human GC tissues compared to adjacent normal tissues. Our study identified mRNA and lncRNA expression profiles related to H. pylori infection. These results may provide important insights regarding lncRNAs in H. pylori-induced gastric carcinogenesis.